2006
DOI: 10.1088/0957-0233/17/9/r01
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric applications of digital signal processing

Abstract: Spectrophotometry is more and more often the method of choice not only in analysis of (bio)chemical substances, but also in the identification of physical properties of various objects and their classification. The applications of spectrophotometry include such diversified tasks as monitoring of optical telecommunications links, assessment of eating quality of food, forensic classification of papers, biometric identification of individuals, detection of insect infestation of seeds and classification of textile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 156 publications
0
6
0
Order By: Relevance
“…These two approaches to solve for the variables are termed the forward-model approach and inverse-model approach [21]. A forward model that transforms the gas concentrations into a spectrum can be built for open-path measurements.…”
Section: The Methods Proposed For the Determination Of Gas Concentratimentioning
confidence: 99%
“…These two approaches to solve for the variables are termed the forward-model approach and inverse-model approach [21]. A forward model that transforms the gas concentrations into a spectrum can be built for open-path measurements.…”
Section: The Methods Proposed For the Determination Of Gas Concentratimentioning
confidence: 99%
“…This methodology may be generalised on the measurands containing some other quantities, provided the corresponding physical, chemical or purely numerical models of the sensitivity of the spectrum    x to those quantities are available. The contents of this and three following sections at many points refer to the author's review paper of 2006 [116], where many more algorithmic details may be found.…”
Section: Mathematical Modelling Of Spectrophotometric Datamentioning
confidence: 99%
“…Tikhonov regularization has been successfully applied to many fields for robustly solving inverse problems of ill-posed conditions. This method has also 1530-437X/$26.00 © 2010 IEEE been presented for improving the resolution of spectrophotometric analyses in the past [8]- [10]. Low complexity and robust methods for selection of the regularization parameter have also received much research attention [11]- [13].…”
Section: Introductionmentioning
confidence: 99%